2005
DOI: 10.1200/jco.2005.01.7145
|View full text |Cite
|
Sign up to set email alerts
|

Early Variations of Circulating Interleukin-6 and Interleukin-10 Levels During Thoracic Radiotherapy Are Predictive for Radiation Pneumonitis

Abstract: Early variations of circulating IL-6 and IL-10 levels during 3D-CRT are significantly associated with the risk of radiation pneumonitis. Variations of circulating IL-6 and IL-10 levels during 3D-CRT may serve as independent predictive factors for this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 40 publications
3
100
1
4
Order By: Relevance
“…The second fibrosis risk factor identified by Giotopoulos et al (34) was to have inherited the transforming growth factor-h1 (TGF-h À509T) single-nucleotide polymorphism (and having undergone radiotherapy), a gene which maps to one of our putative fibrosis linkage intervals. Finally, studies of cancer patients undergoing radiation therapy have revealed bronchoalveolar lavage (35) and serum (8,36,37) levels of TGF-h and IL-6 to be associated with the development of a radiation response, which supports the concept that the mouse pathology correlates with the clinical side effects seen with therapeutic radiation in the cancer patients.…”
Section: Discussionmentioning
confidence: 64%
“…The second fibrosis risk factor identified by Giotopoulos et al (34) was to have inherited the transforming growth factor-h1 (TGF-h À509T) single-nucleotide polymorphism (and having undergone radiotherapy), a gene which maps to one of our putative fibrosis linkage intervals. Finally, studies of cancer patients undergoing radiation therapy have revealed bronchoalveolar lavage (35) and serum (8,36,37) levels of TGF-h and IL-6 to be associated with the development of a radiation response, which supports the concept that the mouse pathology correlates with the clinical side effects seen with therapeutic radiation in the cancer patients.…”
Section: Discussionmentioning
confidence: 64%
“…Though, the functional relevance of lipid droplet formation for radiation-induced pneumopathy remains to be defined. We speculate that as biomarkers for radiation-induced pneumopathy in patients [18,19]. Moreover, a time-dependent increase in tissue levels of TGF-ß, tumor necrosis factor-α, IL-1ß, and IL-6 mRNA as well as of MCP-1 and 3 and MIP-1γ proteins levels has been described in irradiated mice [13,17,20].…”
Section: Discussionmentioning
confidence: 99%
“…13 Interferon-g is reported to be a central mediator of pneumonitis, and 2 independent reports have demonstrated a significant correlation with serum IL-6 and pneumonitis in patients receiving pulmonary radiation. [14][15][16] Although the pathogenesis of PI3K-and mTOR-inhibitor-related pneumonitis has yet to be elucidated, pleiotropic effects on cytokine production have been demonstrated, consistent with a proinflammatory response. 17,18 Further, bronchoalveolar lavage findings of a predominance of CD8 1 T cells may suggest a T-cell-mediated autoimmune response.…”
Section: Org Frommentioning
confidence: 99%